PENGARUH TEKANAN KETAATAN, KOMPLEKSITAS TUGAS, PENGALAMAN, DAN MOTIVASI TERHADAP AUDIT JUDGMENT, GENDER SEBAGAI VARIABEL MODERATING - Janah, Noor; Yuniarto, Arif Sapta (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2013)
This research has a purpose to understand and to analyze the influence of obedient pressure, task complexity, experience, and motivation for audit judgment with gender as moderating variable. From this research, it is able to get empirical evidence about the influence of obedient pressure, task complexity, experience, and motivation for audit judgment. Besides, this research also gives empirical evidence about the difference between man and woman in deciding audit judgment whether it correlates with several factor such as obedient pressure, task complexity, experience, and motivation. In this research, the researcher uses sample for auditors which is serve in the Public Accountant Office in DIY and Semarang. In this research, primary data is used as data, while General Linear Model (GLM) with helping IBM SPSS version 19.0 is used as analysis instrument. The result of this research is to indicate that task complexity influence for audit judgment, while obedient pressure, experience, and motivation do not influence for audit judgment. The issue about gender difference do not also moderate the influence of obedient pressure, task complexity, experience, and motivation for audit judgment.